2012
DOI: 10.1161/strokeaha.111.648568
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lactate Metabolism in Humans With Subarachnoid Hemorrhage

Abstract: Background and Purpose-Lactate is central for the regulation of brain metabolism and is an alternative substrate to glucose after injury. Brain lactate metabolism in patients with subarachnoid hemorrhage has not been fully elucidated. Methods-Thirty-one subarachnoid hemorrhage patients monitored with cerebral microdialysis (CMD) and brain oxygen (PbtO 2 ) were studied. Samples with elevated CMD lactate (Ͼ4 mmol/L) were matched to PbtO 2 and CMD pyruvate and categorized as hypoxic (PbtO 2 Ͻ20 mm Hg) versus nonh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 15 publications
6
97
0
2
Order By: Relevance
“…They report that: "Mortality was associated with increased percentage of samples with elevated lactate and brain hypoxia 28% (interquartile range 9%-95%) in nonsurvivors". This study supports the current clinical practise that pbtO2 below 20mmHg signals cerebral ischemia and may call for therapeutic interventions [217].…”
Section: Definition Of Normal and Pathological Values -A Complex Tasksupporting
confidence: 84%
See 1 more Smart Citation
“…They report that: "Mortality was associated with increased percentage of samples with elevated lactate and brain hypoxia 28% (interquartile range 9%-95%) in nonsurvivors". This study supports the current clinical practise that pbtO2 below 20mmHg signals cerebral ischemia and may call for therapeutic interventions [217].…”
Section: Definition Of Normal and Pathological Values -A Complex Tasksupporting
confidence: 84%
“…There are publications also from Australia [38,[198][199][200], Austria [53,85], Brazil [58], Canada [93,118,132,135,139], China [9, 201,202], Croatia [203], the Czech Republic [204], Denmark [134]; Finland [134], France [43,77,114,205,206], Greece [207], Hungary [141], India [208], Japan [140,146,167,209], Portugal [64]; Russia [210,211], Singapore [2,4,10,16,74,212,213]; Serbia [214]; South Africa [26,28,35], South Korea [127], Sweden [90,134,215], Switzerland [11,216,217]...…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…80,81 Lactate and Clinical Outcome Elevated extracellular lactate levels in 'normal' non-hypoxic white matter after subarachnoid hemorrhage were associated with better outcome compared with patients with hypoxic white matter. 82 Reference was made to lactate metabolism that was not measured in this and the authors' subsequent TBI study, 39 and the rise in lactate level must be due to glucose metabolism. This is an important distinction because the context presented in the introductions and discussions of these reports is that the lactate may be metabolized as neuronal fuel in injured brain.…”
Section: Metabolite Levels Cmr Glc and Cmr O2 After Traumatic Braimentioning
confidence: 91%
“…Consistent with this view, a prior study showed that patients with SAH who had isolated lactate elevations experienced better than expected outcomes, whereas patients in whom elevated lactate coincided with brain hypoxia fared poorly. 43 Finally, extracellular levels of the excitatory neurotransmitter glutamate also correlate with markers of secondary brain injury and poor outcome. 7,65 Seizures and reduced CPP are both associated with abnormally elevated glutamate after TBI.…”
Section: Cerebral Biochemistrymentioning
confidence: 99%